Assessment of the Antibacterial Effect of the Oliveria decumbens vent. Essential Oil on Escherichia coli-induced Cystitis in the Rat Model - Hossein Antikchi; Seeyamak Mashhady Rafie; Negar Panahi; Pejman Mortazavi; kumarss amini (Journal of Sciences, Islamic Republic of Iran)
Antibiotic resistance is among the most concerning issues worldwide. Currently, the use of natural alternatives with improved therapeutic effects and fewer complications than common therapies is considered a novel therapeutic approach to care urinary tract infections (UTI). In this research, we evaluated the prospective activity of Oliveria decumbens vent essential oil (ODEO) in the treatment of Escherichia coli-induced cystitis. The antibacterial properties of ODEO were investigated using standard microdilution assays against E. coli. To induce cystitis, 1.5 ×108  CFU/ml of E. coli (ATCC 700928) was injected into the bladder of Wistar rats, and then they were prescribed ODEO and gentamicin. The histopathological parameters of the bladders were tested at the end of the study. The MIC and MBC of the ODEO against E.coli were 0.54 μl/ml and 1.024 μl/ml respectively. In the infected group with no treatment, the infiltration of inflammatory cells and the thickness of bladder tissue were increased notably, however in the groups treated with ODEO, especially at higher doses, the parameters were significantly decreased (p<0.01). The ODEO efficacy was comparable to gentamicin in the reduction of the bacterial count. In addition, after administration of the ODEO, inflammation, fibrosis, and thickness of epithelium also decreased in a dose-dependent manner (p<0.01). In conclusion, treatment with ODEO which added as drinking supplement or injected subcutaneously resulted to the renal clearance of pathogens in study rats.